The mediating effect of leaders’ emotional intelligence on the relationship between transformational leadership and academics performance in Malaysian public research universities. - Yong, Min Sheng; Chai, Seik Xin (2024)
This research explores the mediating role of leaders' emotional intelligence (EI) in the relationship between transformational leadership (TL) and academics performance in Malaysian Public Research Universities. This study was conducted among 300 academics from five public research universities in Malaysia, namely Universiti Malaya (UM), Universiti Kebangsaan Malaysia (UKM), Universiti Putra Malaysia, (UPM), Universiti Sains Malaysia (USM) and Universiti Teknologi Malaysia (UTM). Grounded in social exchange theory and social learning theory, the study examines how EI influences leadership behavior and enhances academics performance. A total of 400 questionnaires were distributed, with 300 valid responses collected. The data were analyzed using SPSS, employing descriptive analysis, reliability testing, normality testing, Pearson Correlation Coefficient Analysis, and Multiple Linear Regression. The results indicate that leaders' emotional intelligence significantly mediates the relationship between transformational leadership and academics performance. These findings provide valuable insights into leadership development in higher education institutions, suggesting that enhancing leaders' emotional intelligence can improve academic outcomes. It is anticipated that the findings of this study will assist policymakers, the Ministry of Higher Education (MOHE), university management, and researchers in developing and enforcing policies and practices aimed at strengthening academic leadership and improving the performance of subordinates in Malaysian Public Research Universities. Keywords: Transformational leadership, emotional intelligence, academics and performance